2005
DOI: 10.1155/jbb.2005.198
|View full text |Cite
|
Sign up to set email alerts
|

Metabolite Fingerprinting in Transgenic Nicotiana tabacum Altered by the Escherichia coli Glutamate Dehydrogenase Gene

Abstract: With about 200 000 phytochemicals in existence, identifying those of biomedical significance is a mammoth task. In the postgenomic era, relating metabolite fingerprints, abundances, and profiles to genotype is also a large task. Ion analysis using Fourier transformed ion cyclotron resonance mass spectrometry (FT-ICR-MS) may provide a high-throughput approach to measure genotype dependency of the inferred metabolome if reproducible techniques can be established. Ion profile inferred metabolite fingerprints are … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
58
0
3

Year Published

2006
2006
2018
2018

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 96 publications
(66 citation statements)
references
References 38 publications
5
58
0
3
Order By: Relevance
“…GS2 is crucial for the reassimilation of this NH 4 1 , because mutants lacking this enzyme accumulate NH 4 1 and die (Wallsgrove et al, 1987). Although GDH activity is usually very low in mesophyll cells compared with GS2 (Bechtold et al, 1998), several studies have provided evidence that mesophyll GDH may reassimilate small amounts of photorespiratory NH 4 1 (Hartmann and Ehmke, 1980;Neeman et al, 1985;Yamaya et al, 1986 1 ] produce more labeled Glu and Gln than controls (Ameziane et al, 2000;Mungur et al, 2005). Combined, these results provide strong evidence that the pool of E. coli GDH in these transformants reassimilates photorespiratory NH 4 1 .…”
Section: Gdh Isoenzyme 1 In Roots Catabolizes Glumentioning
confidence: 99%
“…GS2 is crucial for the reassimilation of this NH 4 1 , because mutants lacking this enzyme accumulate NH 4 1 and die (Wallsgrove et al, 1987). Although GDH activity is usually very low in mesophyll cells compared with GS2 (Bechtold et al, 1998), several studies have provided evidence that mesophyll GDH may reassimilate small amounts of photorespiratory NH 4 1 (Hartmann and Ehmke, 1980;Neeman et al, 1985;Yamaya et al, 1986 1 ] produce more labeled Glu and Gln than controls (Ameziane et al, 2000;Mungur et al, 2005). Combined, these results provide strong evidence that the pool of E. coli GDH in these transformants reassimilates photorespiratory NH 4 1 .…”
Section: Gdh Isoenzyme 1 In Roots Catabolizes Glumentioning
confidence: 99%
“…When high-resolution NMR methods are coupled to multivariate statistical analysis, the resulting partitions give unambiguous information about influences of nutritional and genetic backgrounds (Ratcliffe and Shachar-Hill, 2001;Mannina et al, 2003;Amato et al, 2004;Krishnan et al, 2005). Metabolite profiling, metabolomics, offers a powerful approach to monitor complexity of genetically modified crops and document any unintended consequences of a modified gene introduced in crops (Kuiper et al, 2001;Sumner et al, 2003;Tretheway, 2004;Mungur et al, 2005). We have used high-resolution NMR methods to generate an analysis of the principal, soluble constituents of wildtype and polyamine-accumulating transgenic tomato.…”
mentioning
confidence: 99%
“…In transgenic tobacco plants with the gdhA transgene, 13 N labeling of glutamate and glutamine increased significantly (Mungur et al 2005). We also reported that the glutamate content of the fruits of the transgenic tomato plants that harbored a gdhA gene for NADPH-dependent GDH from Aspergillus nidulans was approximately twice that of the wild type (Kisaka and Kida 2003).…”
Section: Introductionmentioning
confidence: 73%